Detecting oxidative stress in leaves of apple tree and white clover by analysis of ascorbic acid and pigments using high performance liquid chromatography - Helena ŠIRCELJ; Franc BATIČ (Acta Agriculturae Slovenica)
Ascorbic acid and photosynthetic pigments content in leaves of the apple tree (Malus domestica Borkh.) subjected to drought and white clover (Trifolium repens L.) exposed to high ozone concentrations were measured by high performance liquid chromatography in order to detect oxidative stress. Measurements showed a significant difference between stressed and control plants. Water deficit increased ascorbic acid and zeaxanthin, and decreased total chlorophyll (a+b) and b-carotene in apple tree leaves. High concentrations of ozone increased ascorbic acid, total carotenoids, neoxanthin, zeaxanthin and b-carotene, and decreased violaxanthin and antheraxanthin in white clover leaves. Observed changes in ascorbic acid and photosynthetic pigment content in leaves of tested apple tree and white clover plants indicate that oxidative stress may have occured under stress conditions used in our experiments.